Aplikasi Biosand Filter Dengan Penambahan Media Karbon (Arang Kayu) Untuk Pengolahan Air Sumur Daerah Gambut - Okdika Berliandra; Yohanna Lilis Handayani; Lita Darmayanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Refers to the results test from UPT Health and Environment Laboratory in Pekanbaru, the quality of water wells in peat areas on Kadiran Street RW.06 / RT.03, Kulim, Tenayan Raya District, Pekanbaru City, has turbidity (CaCO3) level of 18 mg/L and contains iron metal (Fe) < 0,0195 mg/L, manganese (Mn) < 0,0248 mg/L, organic substances (KMnO4) 9,7 mg/L, pH levels between of 4.9 – 5.2, and smelling. This condition makes water wells in peat areas should through processing water treatment before consumed. Biosand filter with the addition of carbon (charcoal) is the one of alternative treatment for water wells in peat areas with simple and natural concept. The purpose of this research for determining the efficiency from using biosand filter with the addition of carbon (charcoal) to get the most quality of water wells in peat areas based on the parameters pH, smelling, and organic substances. Reactor of biosand filter is made from PVC pipe diameter of 6" and high 150 cm. The results showed that, biosand filter produces the best efficiency to increase the pH value up to 26.00%, to decrease organic substances value up to 91.92%, and eliminates of smelling. In generally, water wells in peat areas which produced by biosand filter process can to repair the parameters of the organic substances and smelling. However water discharge producing from reactor of biosand filter is too small, so that not effective to be applied.Keywords: water wells, biosand filter, charcoal